Pulmonary Tuberculosis Mimicking Pulmonary Metastases - Pinos Vélez, Nathalie (2026)
Introduction: Tuberculosis (TB) is an infectious disease caused by the Mycobacterium tuberculosis. The disease can present in the chest as pulmonary infiltrates and/or mediastinal lymphadenopathy, The TB is a disease who has a special ability to mimic other pathologies, including malignancies. Case report: We present the case of a 36-year-old male with bilateral symbrachydactyly, residing in Ecuador. The patient presented with a two-month history of dry cough. A non-contrast chest CT scan revealed multiple bilateral subcentimeter pulmonary nodules. Due to the high suspicion of a metastatic disease, a biopsy of one of the pulmonary nodules through surgical biopsy was performed, showing caseating granulomas in the histopathological study. A multidisciplinary committee decided to iniciate tuberculosis treatment based on the standard 2HREZ/4HR regimen, in the following weeks the patient showed significant symptomatic improvement and positive tuberculosis culture at 12 weeks. A follow-up CT scan at six months showed complete resolution of the pulmonary lesions. Conclusion In countries with a high incidence of tuberculosis, clinical suspicion is sufficient to start specific treatment until cultures confirm the disease.